Forced to work from home: Division of unpaid work between parents and the relation to job satisfaction - Santos, M. H.; Rosa, M.; Correia, R. B.; Ramos, J.; Carvalho, A. C. (Social Sciences, 2023)
This study investigates the division of household chores and caregiving tasks during the COVID-19 pandemic, considering the influence of participants’ sex, work arrangement, and parental status. Additionally, it aims to understand the relationship of these variables with job satisfaction. Specifically, this study analyses the role of participants’ sex and parental status in the increase and division of unpaid work and investigates the roles of sex, work arrangements (namely telework and on-site work), and the division of unpaid work in job satisfaction. These variables were measured and analyzed with a sample of 268 workers in Portugal (57.8% of whom were teleworking) during pandemic lockdowns. Taken together, the results suggest that despite prepandemic advances in gender equality and despite men and women perceiving an increase in their domestic workload during lockdowns, there were significant inequalities between men and women in the division of unpaid work. These were intensified for couples with young children and were not mitigated by changes in work arrangements such as telework. For women, the lack of sharing in caregiving tasks while teleworking decreased their job satisfaction. For them, the lack of sharing of caregiving tasks moderates the relationship between work arrangements and job satisfaction. The same was not true for men. Despite the optimistic view that telework might promote a more equal sharing of unpaid work, this study shows that unpaid work is still mostly performed by women, with important consequences for the paid work sphere.